2004
DOI: 10.1159/000081637
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Characterization of Human Amniotic Membrane Preparations for Ocular Surface Reconstruction

Abstract: Purpose: To investigate the tensile and elastic properties of both commercially available and experimental human amniotic membrane preparations. Method: Nine preparations of human amniotic membrane were studied. The four dry preparations were untreated (nonirradiated, n = 20), and gamma (n = 25), low-dose (AmbioDry®, Okto Ophtho Inc., Costa Mesa, Calif., USA, n = 20) and high-dose (n = 20) electron beam sterilized. The same dry membranes were moistened with balanced salt solution (n = 20, 34, 20 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 60 publications
3
24
1
Order By: Relevance
“…Chuck et al 36 reported that the mechanical characterization of HAM was very weak; however, in our study, we measured the tensile strength of HAM (rolled into an 8 mm diameter cylinder) to be 1331 AE 179 N (data not shown). We think the two results could not be directly compared because the methods of analysis methods were different, including the condition of used HAM (wet and fresh HAM was used in our study) and its thickness (100-200 mm in our study).…”
Section: Discussioncontrasting
confidence: 53%
“…Chuck et al 36 reported that the mechanical characterization of HAM was very weak; however, in our study, we measured the tensile strength of HAM (rolled into an 8 mm diameter cylinder) to be 1331 AE 179 N (data not shown). We think the two results could not be directly compared because the methods of analysis methods were different, including the condition of used HAM (wet and fresh HAM was used in our study) and its thickness (100-200 mm in our study).…”
Section: Discussioncontrasting
confidence: 53%
“…Indications of amniotic membrane transplantation for treatment of ocular surface diseases have ranged from cicatricial ocular surface disorders such as Stevens–Johnson syndrome, alkali burn, bullous or band keratopathy, ocular cicatricial pemphigoid to pterygium and conjunctival tumors [21, 22]. Fresh or preserved amniotic membrane has been shown to promote epithelization, reduce inflammation, prevent neovascularization and suppress recurrent subconjunctival fibrosis following symblepharon lysis [2123] Furthermore, amniotic membrane is known to differentiate into conjunctival epithelial cells [24]. Additionally, recent advances in the use of fibrin glue in conjunction with amniotic membrane transplantation has significantly enhanced the application of tissues adhesives in ocular surface reconstruction [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…However, as the AM is a human-derived tissue, it is a potential vector for transferring infectious disease [11]. Other drawbacks of using this biological material have also been reported [12][13][14]. Therefore, the search for alternative materials is increasingly important.…”
Section: Introductionmentioning
confidence: 99%